Enhanced Derivative-Free Conjugate Gradient Method for Solving Symmetric Nonlinear Equations - Jamilu Sabi'u (International Journal of Advances in Applied Sciences, 2016)
In this article, an enhanced conjugate gradient approach for solving symmetric nonlinear equations is propose without computing the Jacobian matrix. This approach is completely derivative and matrix free. Using classical assumptions the proposed method has global convergence with nonmonotone line search. Some reported numerical results shows the approach is promising.